Antiresorptive treatment and talar collapse after displaced fractures of the talar neck: a long-term follow-up of 19 patients - Meunier, Andreas; Palm, Lars; Aspenberg, Per; Schilcher, Jörg (Acta Orthopaedica, 2021)
Background and purpose — Displaced fractures of the talar neck are associated with a high risk of structural collapse. In this observational analysis we hypothesized that pharmacological inhibition of osteoclast function might reduce the risk of structural collapse through a reduction in bone resorption during revascularization of the injured bone. Patients and methods — Between 2002 and 2014 we treated 19 patients with displaced fractures of the talar neck with open reduction and internal fixation. Of these, 16 patients were available for final follow-up between January and November 2017 (median 12 years, IQR 7–13). Among these, 6 patients with Hawkins type 3 fractures and 2 patients with Hawkins type 2b fractures received postoperative antiresorptive treatment (7 alendronate, 1 denosumab) for 6 to 12 months. The remaining 8 patients received no antiresorptive treatment. The self-reported foot and ankle score (SEFAS) was available in all patients and 15 patients had undergone computed tomography (CT) at final follow-up, which allowed evaluation of structural collapse of the talar dome and signs of post-traumatic osteoarthritis. Results — The risk for partial collapse of the talar dome was equal in the 2 groups (3 in each group) and post-traumatic arthritis was observed in all patients. The SEFAS in patients with antiresorptive treatment was lower, at 21 points (95% CI 15–26), compared with those without treatment, 29 points (CI 22–35). Interpretation — Following a displaced fracture of the talar neck, we found no effect of antiresorptive therapy on the rate of talar collapse, post-traumatic osteoarthritis, and patient-reported outcomes.